Emergence of Lumpy Pox Virus and Their Preventive Measures: A Global Livestock Threat - Dhasmana, Archna; Bhandari, Geeta; Joshi, Nupur; Jadon , Vikash Singh; Rawat, Jyoti; Khatkar , Lavish; Gupta, Sanjay (Journal of Advanced Zoology, 2023)
In the last few years viral disease not only affect the human but also the other life on this planet and result epidemic condition at global level. The highly transmissible viral disease called Lumpy skin disease (LSD) spread in sequential manner at worldwide level affecting the cattle or dairy animals of caprine, ovine and bovine family. The highly mutational efficiency of this viral strains affects the large-scale population and still no effective cure for it. Different vaccines designed at national and international level as a preventive measure to overcome the reoccurrence of this virus e.g., Bovivax-LSD™, Lumpivax™, Poxvac™, Lumpi-ProVacInd. However, still the mortality of LSD are low, not affect humans but emergence of the mutational variants demands novel vaccines.